Ulnolunate Ligament Avulsion Fracture of the Lunate: A Case Report - Sato, Ryosuke; Hibino, Naohito; Hamada, Yoshitaka; Sairyo, Koichi (Journal of Wrist Surgery, 2017)
Traumatic lunate fractures are very rare and those treatments require an understanding of anatomical features. We present a case of an ulnolunate ligament avulsion fracture of the lunate that was successfully repaired by surgical fixation with open reduction and internal fixation. We believe that restoration of ulnolunate ligament function is important to prevent further deterioration of wrist function after this injury.
Keywords: traumatic lunate fracture; ulnolunate ligament; surgical treatment; carpal injuries; intercarpal ligament